First Glycine Isomer Detected in the Interstellar Medium: Glycolamide (NH2C(O)CH2OH) - Víctor M. Rivilla; Miguel Sanz-Novo; Izaskun Jiménez-Serra; Jesús Martín-Pintado; Laura Colzi; Shaoshan Zeng; Andrés Megías; Álvaro López-Gallifa; Antonio Martínez-Henares; Sarah Massalkhi; Belén Tercero; Pablo de Vicente; et al. (The Astrophysical Journal Letters, 2023)
We report the first detection in the interstellar medium (ISM) of a C _2 H _5 O _2 N isomer: syn -glycolamide (NH _2 C(O)CH _2 OH). The exquisite sensitivity at sub-mK levels of an ultradeep spectral survey carried out with the Yebes 40 m and IRAM 30 m telescopes toward the G+0.693–0.027 molecular cloud has allowed us to unambiguously identify multiple transitions of this species. We derived a column density of (7.4 ± 0.7) × 10 ^12 cm ^−2 , which implies a molecular abundance with respect to H _2 of 5.5 × 10 ^−11 . The other C _2 H _5 O _2 N isomers, including the higher-energy anti conformer of glycolamide and two conformers of glycine, were not detected. The upper limit derived for the abundance of glycine indicates that this amino acid is surely less abundant than its isomer glycolamide in the ISM. The abundances of the C _2 H _5 O _2 N isomers cannot be explained in terms of thermodynamic equilibrium; thus, chemical kinetics need to be invoked. While the low abundance of glycine might not be surprising, based on the relative low abundances of acids in the ISM compared to other compounds (e.g., alcohols, aldehydes, or amines), several chemical pathways can favor the formation of its isomer glycolamide. It can be formed through radical–radical reactions on the surface of dust grains. The abundances of these radicals can be significantly boosted in an environment affected by a strong ultraviolet field induced by cosmic rays, such as that expected in G+0.693–0.027. Therefore, as shown by several recent molecular detections toward this molecular cloud, it stands out as the best target to discover new species with carbon, oxygen, and nitrogen with increasing chemical complexity.